The Future of Innovative Agriculture: Bioeconomy and Sustainable Agriculture - Mutlu Bulut; Gökhan Filik (Turkish Journal of Agriculture: Food Science and Technology)
Innovative farming techniques are essential for food security and sustainable farming practices. Innovative agricultural approaches utilize modern technologies and the latest inventions, as well as traditional agricultural practices. The main purpose of this study is to address the relationship between sustainable agriculture and bioeconomy and to examine innovative approaches that are expected to have a significant impact on the agricultural sector in the near future. The study was carried out in compilation format. Bioeconomy is an economic model or methodology based on the economic evaluation of biological resources and processes. Abiotic resources such as microbes, vegetation, animals, and biodiversity are all included in this strategy. On the other hand, sustainable agriculture, which aims to protect natural resources and take into account ecosystem benefits while maintaining food production, is an agricultural paradigm. The primary goals of bioeconomy and sustainable agriculture are economic evaluation, efficient use of natural resources and reduction of environmental impacts. Considered from these perspectives, it can be said that both concepts have common purposes and are closely related. It is possible to say that with the increasing use of sustainable agricultural methods and bioeconomy, the agricultural sector can move towards a more environmentally friendly, efficiently managed and sustainable structure in the future.